2018
DOI: 10.1021/acs.cgd.8b01151
|View full text |Cite
|
Sign up to set email alerts
|

Polymorph Selection via Sublimation onto Siloxane Templates

Abstract: Diphenylurea (PU) crystallizes via slow evaporation from a range of solvents as phase pure α-PU or in a concomitant mixture with the less stable β-PU phase. Sublimation onto glass also yields α-PU in high phase purity. In contrast, sublimation onto siloxane-coated glass templates with various terminal groups (e.g., isocyanate, acetate, bromine) resulted in primarily β-PU. Scanning electron microscopy showed that the individual crystals on siloxanes exhibit a range of different morphologies (e.g., plates, needl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 57 publications
(64 reference statements)
0
16
0
Order By: Relevance
“…Previous work has demonstrated that it is possible to template the growth of a particular form and discover new polymorphs by subliming onto different surfaces, e.g ., polycrystalline powders, 76 siloxane-coated glass, 65 and crystals with related structure. 32 , 33 Both Forms I and II of IPN display different hydrogen bonding patterns to the known form of ISN and hence crystals of one compound could be used to template the growth of new forms of the other analogue.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has demonstrated that it is possible to template the growth of a particular form and discover new polymorphs by subliming onto different surfaces, e.g ., polycrystalline powders, 76 siloxane-coated glass, 65 and crystals with related structure. 32 , 33 Both Forms I and II of IPN display different hydrogen bonding patterns to the known form of ISN and hence crystals of one compound could be used to template the growth of new forms of the other analogue.…”
Section: Resultsmentioning
confidence: 99%
“…In turn, Patel et al in their paper described a new method called Predicting Efficacy Through Intermolecular Interactions (PETI) for predicting the effectiveness of different polymer surfaces in promoting heterogeneous nucleation [ 24 ]. Solomos et al crystallized diphenylurea via slow evaporation from a range of solvents [ 25 ]. The experiments demonstrated the utility of template-directed sublimation methods as a way to obtain metastable phases with high phase purity.…”
Section: Basic Researchmentioning
confidence: 99%
“…60 As a result, sublimation experiments were also undertaken as they have previously been used to crystallize the formation of metastable forms. [61][62][63] ISN was sublimed by heating on a microscope stage below its melting point (171.4°C) at relatively high heating rates (5 and 10 °C/min). A borosilicate glass coverslip was placed above the sample and the ISN vapour crystallized on the colder coverslip.…”
Section: Experimental Crystallization Of Isn and Ipnmentioning
confidence: 99%
“…Previous work has demonstrated that it is possible to template the growth of a particular form and discover new polymorphs by subliming onto different surfaces, e.g. polycrystalline powders, 71 siloxane-coated glass 61 and crystals with related structure. 32,33. Both Forms I and II of IPN display different hydrogen bonding patterns to the known form of ISN and hence crystals of one compound could be used to template the growth of new forms of the other analogue.…”
Section: Templated Sublimationsmentioning
confidence: 99%